New features of pertussis vaccination - A. P. Cherdantsev; E. V. Prutskova; M. P. Kostinov (LLC "Diagnostics and Vaccines", 2020)
The review provides information about the current features of the spread of whooping cough among children and adolescents. It is shown that there is a shift in morbidity to an older age group of the population, which is facilitated by changes in the properties of the pathogen and the widespread use of drugs based on cell-free technology as primary vaccination. Information is given about the possibility of preventing morbidity among schoolchildren and adults by introducing additional revaccinating doses against whooping cough with special drugs in the vaccination calendars. Information is given on effective protection of newborns against this infection by immunization of pregnant women. In our country, there is an opportunity to expand pertussis immunoprophylaxis among children of preschool-school age and adults within regional programs and individual vaccination with acellular pertussis-diphtheria-tetanus vaccines, which has a high profile of safety and immunological effectiveness.